Pseudomonas aeruginosa-Mediated Damage Requires Distinct Receptors at the Apical and Basolateral Surfaces of the Polarized Epithelium - Bucior, Iwona (American Society for Microbiology (ASM), 2010)
Pseudomonas aeruginosa, an important opportunistic pathogen of humans, exploits epithelial damage to establish infection. We have rigorously explored the role of N-glycoproteins and heparan sulfate proteoglycans (HSPGs) in P. aeruginosa-mediated attachment and subsequent downstream events at the apical (AP) and basolateral (BL) surfaces of polarized epithelium. We demonstrate that the N-glycan chains at the AP surface are necessary and sufficient for binding, invasion, and cytotoxicity to kidney (MDCK) and airway (Calu-3) cells grown at various states of polarization on Transwell filters. Upregulation of N-glycosylation enhanced binding, whereas pharmacologic inhibition of N-glycosylation or infection of MDCK cells defective in N-glycosylation resulted in decreased binding. In contrast, at the BL surface, the HS moiety of HSPGs mediated P. aeruginosa binding, cytotoxicity, and invasion. In incompletely polarized epithelium, HSPG abundance was increased at the AP surface, explaining its increased susceptibility to P. aeruginosa colonization and damage. Using MDCK cells grown as three-dimensional cysts as a model for epithelial organs, we show that P. aeruginosa specifically colocalized with HS-rich areas at the BL membrane but with complex N-glycans at the AP surface. Finally, P. aeruginosa bound to HS chains and N-glycans coated on plastic surfaces, showing the highest binding affinity toward isolated HS chains. Together, these findings demonstrate that P. aeruginosa recognizes distinct receptors on the AP and BL surfaces of polarized epithelium. Changes in the composition of N-glycan chains and/or in the distribution of HSPGs may explain the enhanced susceptibility of damaged epithelium to P. aeruginosa.